Optimation of Fe3+ Ion Desorption Using Sulfonate Modified Silica Gel-GPTMS - Elvina, Elvina; Oktavia, Budhi; Nasra, Edi; Zainul, Rahadian (Jurnal Pijar Mipa, 2024)
Silica gel is one of the adsorbents widely used in adsorption, but silica gel has a low ability to absorb metals. Hence, modifications need to be made to improve it. Silica gel modified using sulfonate groups from monosodium salt compound of 4-amino-5-hydroxy-2,7-naphthalene disulfonic acid using GPTMS coupling compound for adsorption and desorption of Fe3+ ions by column method was carried out. The adsorption process of Fe3+ ions using silica gel-GPTMS-sulfonate has been carried out in previous studies and obtained an optimum state at pH 6 and a concentration of 20 ppm. After the adsorption process is carried out, the desorption process is continued with variations in the type of desorption eluent and concentration variations. The types of desorption agents are NaCl, CaCl2, HCl, and HNO3, with the optimum desorption agent being HNO3 with a release of 0.077517 mg of Fe3+ ions from 0.1587403 mg of Fe3+ ions absorbed and a desorption percentage of 48.83%. The concentration variations are 0.5 M, 1 M, 2.5 M, and 5 M, with an optimum concentration of 2.5 M HNO3 with a release of 0.098505 mg Fe3+ ions and a desorption percentage of 64.43%.